PERANCANGAN DNA POLIMERASE THERMUS AQUATICUS MUTAN TERMOSTABIL DENGAN PENINGKATAN FIDELITAS DAN AKTIVITAS REVERSE TRANSKRIPTASE - Cindy, Agatha
DNA polymerase is used in polymerase chain reaction (PCR) to synthesize new DNA strands. DNA polymerase uses a DNA template to direct DNA synthesis. Reverse transcriptase (RTase) is needed as an additional enzyme in RNA-based diagnoses, such as pathogen detection and gene expression analysis because DNA polymerase does not accept RNA templates. The RTase enzyme which is thermolabile and has low fidelity causes reverse transcription to be less optimal. The aim of this study was to produce mutant Thermus aquaticus DNA polymerase sequences with increased fidelity and RTase activity. The thermostable mutant DNA polymerase family A T. aquaticus sequence (Taq M2) was designed by substituting 4 residual polymerase domains (L459M, S515R, I638F, M747K) and replacing 3’?5’exonuclease domains with high fidelity domains of family B DNA polymerase Pyrococcus furiosus. The comparison sequence (Taq M1) was designed without replacement of the correction domain to determine the effect of replacement of the correction domain on RTase activity in the polymerase domain of Taq M2. The DNA polymerase sequence design was analyzed using a 3D structural approach. Homology modeling with SWISSMODEL was carried out using T. aquaticus DNA polymerase template (PDB ID: 1TAQ). The structure of the modeling results was then refined using Galaxy Refinement. Validation of structures with MolProbity shows that the structural model was reliable. Docking of Taq M1 and Taq M2 against duplex primary-RNA with HADDOCK showed that both structures could accept RNA template with similar positions and conformations. It showed that the replacement of the 3'-5 'exonuclease domain did not affect the RTase activity in the polymerase domain. The results of the interaction analysis with PyMOL showed that 5 of the same 6 amino acid residues in Taq M1 and Taq M2 interacted with the primers, and 5 of the 8 same amino acid residues interacted with the RNA template. The results of docking and interaction analysis showed the Taq M2 sequence with increased fidelity and RTase activity. Codon optimization results of Taq M2 sequence with Escherichia coli (BL21)DE3 as host cell was acceptable with CAI value of 0.745 and GC percentage of 52%.